Trichomes and photosynthetic pigment composition changes: responses of Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L. to Mediterranean stress conditions (Trees, 2002)
Sun and shade leaves of two Mediterranean Quercus species, Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L., were compared by measuring leaf optical properties, photosynthetic pigment composition and photosystem II efficiency. The presence of trichomes in the adaxial (upper) leaf surface of Q. ilex subsp. ballota seems to constitute an important morphological mechanism that allows this species to maintain a good photosystem II efficiency during the summer. Q. coccifera has almost no trichomes and seems instead to develop other physiological responses, including a smaller light-harvesting antenna size, higher concentrations of violaxanthin cycle pigments and a higher (zeaxanthin + antheraxanthin)/(violaxanthin + antheraxanthin + zeaxanthin) ratio. Q. coccifera was not able to maintain a good photosystem II efficiency up to the end of the summer. In Q. ilex subsp. ballota leaves, natural loss or mechanical removal of adaxial-face leaf trichomes induced short-term decreases in photosystem II efficiency. These changes were accompanied by deepoxidation of violaxanthin cycle pigments, suggesting that the absence of trichomes would trigger physiological responses in this species. Our data have revealed different patterns of response of Q. ilex subsp. ballota and Q. coccifera facing the stress conditions prevailing in the Mediterranean area.

Differences in the response of carbon assimilation to summer stress (water deficits, high light and temperature) in four Mediterranean tree species (Physiologia Plantarum, 1998)
Daily changes in photoprotective mechanisms were studied in sun leaves of Quercus suber L., Quercus ilex L., Olea europaea L. and Eucalyptus globulus Labill. trees during the summer in Portugal. Even though stomatal closure explained most of the diurnal variation in carbon assimilation along the summer, a decline in the photochemical yield of photosystem II (F′v/F′m) also occurred, as a result of an excess of intercepted solar radiation when carbon assimilation is limited by stomatal closure due to high vapour pressure deficits and/or soil water deficits. These changes were accompanied by the conversion of violaxanthin to antheraxanthin and zeaxanthin which were correlated with thermal dissipation of excess photon energy. In spite of a common general response, differences between species were observed -Olea europaea, which is a slow-growing tree, had the lowest net photosynthetic rates, the highest proportion of carotenoids in relation to chlorophyll and the highest rates of de-epoxidation of violaxanthin. This enabled a large thermal dissipation of the excess intercepted radiation but led to rather small values of light utilisation for photochemistry (ca 20%). In contrast, in E. globulus, a fast-growing tree, photosynthetic rates were the highest, thermal dissipation of absorbed radiation the lowest and maximal values of light utilisation for photochemistry reached ca 50%. The two Quercus species exhibited an intermediate response. A high degree of co-ordination is apparent between stomatal behaviour, photosynthetic capacity and photoprotection mechanisms.

Seasonal changes in xanthophyll composition and photosynthesis of cork oak (Quercus suber L.) leaves under mediterranean climate (Journal of Experimental Botany, 1997)
Seasonal changes in pigment composition of sun and shade leaves of cork oak (Quercus suber) were studied under field conditions in Portugal. Expanding leaves showed a high concentration of xanthophyll cycle components, violaxanthin, antheraxanthin and zeaxanthin. The pool of violaxanthin plus antheraxanthin plus zeaxanthin (V+A+Z) varied greatly between the seasons, being higher at the end of summer and in winter when photosynthesis was limited by water stress and cold, respectively. The size of V+A+Z pool was associated to synthesis of zeaxanthin in response to an excess of light. In sun leaves, midday A+Z relative content was positively correlated with the V+A+Z pool, whereas in shade leaves A+Z decreased with leaf ageing. In both leaf types A+Z was positively correlated with the non-photochemical quenching (NPQ) of chlorophyll a fluorescence. However, in winter NPQ did not change significantly throughout the day, whereas the (A+Z)/(V+A+Z) increased following the typical daily trend observed in other seasons.
10.1093/jxb/48.9.1667